2019
DOI: 10.1186/s13195-019-0509-9
|View full text |Cite
|
Sign up to set email alerts
|

Frailty effects on non-demented cognitive trajectories are moderated by sex and Alzheimer’s genetic risk

Abstract: Background: Age-related frailty reflects cumulative multisystem physiological and health decline. Frailty increases the risk of adverse brain and cognitive outcomes, including differential decline and dementia. In a longitudinal sample of non-demented older adults, we examine whether (a) the level and/or change in frailty predicts trajectories across three cognitive domains (memory, speed, and executive function (EF)) and (b) prediction patterns are modified by sex or Alzheimer's genetic risk (Apolipoprotein E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 69 publications
6
27
1
Order By: Relevance
“…Frailty and cognitive impairment are distinguishable facets of aging that interact in the cycle of age-related decline. Our results indicated that in cognitively normal older adults, frailty status was associated with aging-related cognitive declines at-risk for the preclinical phase of cognitive disorders, and consistent with previous studies (7)(8)(9)(10)(11). In their seminal study, Solfrizzi and colleagues reported that frail older adults had a higher prevalence of cognitive impairment than those without frailty (77% vs. 54%) (37).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Frailty and cognitive impairment are distinguishable facets of aging that interact in the cycle of age-related decline. Our results indicated that in cognitively normal older adults, frailty status was associated with aging-related cognitive declines at-risk for the preclinical phase of cognitive disorders, and consistent with previous studies (7)(8)(9)(10)(11). In their seminal study, Solfrizzi and colleagues reported that frail older adults had a higher prevalence of cognitive impairment than those without frailty (77% vs. 54%) (37).…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings extend the literature by describing different patterns of associations of MBI and its components with frailty, a pattern not previously established. Prior studies of the link between frailty and cognition have focused on individual functional abilities and assessed only global cognitive ability or limited cognitive domains (9,52). The mechanisms for the association is not clear, but possibly involves abnormalities in biological processes related to aging (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty may increase the risk of future cognitive decline and that cognitive impairment may increase the risk of frailty suggesting that cognition and frailty may interact in the cycle of age-related decline (54,55). Our results indicated that frailty was associated with aging-related cognitive declines at-risk for the preclinical phase of neurocognitive disorders, and consistent with previous studies (11)(12)(13)(14)(15)(16). In their seminal study, Solfrizzi and colleagues reported that frail older adults had a higher prevalence of cognitive impairment than those without frailty (77% vs. 54%) (56).…”
Section: Discussionsupporting
confidence: 90%
“…Frailty that combines a range of diverse de cits, is increasingly recognized as a fundamental determinant of an individual's vulnerability or resilience to stressors (9) and has been linked to impaired cognition (10,11). Various neurocognitive disorders, including late-life cognitive impairment(12, 13), mild cognitive impairment (MCI) (14), dementia (15) and Alzheimer's disease (AD) (16,17), have been shown to be associated with frailty. Researchers have also found that frailty and cognitive decline might share common physiological mechanisms, with greater frailty being associated with worse cognition and a faster rate of cognitive decline (18).…”
Section: Introductionmentioning
confidence: 99%